THE ETYMOLOGY OF ENGLISH AND UZBEK RIDDLES - Tursunova Nilufar Shodikul qizi (Scholar Express Journals, 2025)
The linguistic and cultural analysis of the connotative meanings in the riddles helps to study the unique imaginations, worldviews and values of each nation through them. Connotative meaning refers to additional emotional, social and cultural meanings associated with a word in addition to its lexical meaning. Linguistic analysis includes the analysis of connotations from the point of view of culture and language units.
Keywords: Etymology; Riddles; English Language